Exploring The Determinants of Supply Chain Social Sustainability Disclosure for Indonesian Banking - Frihardina Marsintauli; Eka Novianti; Roni Patar Situmorang (JOIV : International Journal on Informatics Visualization, 2023)
Supply chain transformation that focuses on sustainability encourages companies not only for business growth but also to improve the welfare of the people along the supply chain. The company considers business decisions to reduce environmental impacts arising from the supply chain and positively impact society. Banking has a close relationship with technological developments that strongly support the banking business processes in producing customer services. This study aimed to identify and analyze the factors that influence a banking sector's disclosure of a sustainability report. This quantitative research uses data processing with multiple regression analysis by using SPSS. The research object is a company engaged in the financial services sector listed on the Indonesia Stock Exchange in 2017-2019 with a purposive sampling method. This study indicates that only foreign ownership has influenced sustainability report disclosure. In contrast, profitability, leverage, the board of directors, and the audit committee have no effect. Characteristics and culture of foreign parties who are very concerned about the future risk of the business activities believed able to encourage Indonesian Banking to make changes to business processes and tend to pay attention to the resulting business impact and weigh the business risks that arise in the future. This will lead to sustainable changes in the company and the stakeholders in the utilization of resources, processes, and business outputs generated. Banking in Indonesia should transform into a supply chain strategy concerned with the quality of disclosure of the company's business sustainability on social, environmental, and economic aspects